Representaciones sociales que le otorgan a la justicia los adolescentes del centro de atención especializada en Leticia -Amazonas (2020)
This research work aimed to describe the social representations of adolescents who are institutionalized in the specialized care center, compared to what is understood by justice, mainly due to the increase in the numbers of young people who are in conflict with the law.